‘The “Meidias” hydria: a visual and textual journey of a Greek vase in the history of art of antiquity (c. 1770s–1840s)’ - Emmanouil Kalkanis (Journal of Art Historiography, 2013)
This article examines scholarly publications between the 1770s and 1840s of one of the most published Athenian red-figured vases, a hydria first known in the collection of Sir William Hamilton and since 1772 in the British Museum. It reviews critically several visual and textual interpretations of the vase by a range of scholars of various European nationalities. It offers a new interpretation of a well-known object and reveals the extent to which its iconography influenced the development of art-historical writing and vice versa. While d’Hancarville was a pioneer in his own peculiar way, others were all more or less influenced by him though having their own agendas, not really related to any intrinsic interest in the vase, or any vase, as an object. What the article establishes is that although every writer was the product of his time and culture, only one of them (Eduard Gerhard) really advanced the study of the vase or Greek ceramics being more thorough and imaginative in analyzing the subject matter.